2012
DOI: 10.1002/cne.23098
|View full text |Cite
|
Sign up to set email alerts
|

Distinct retinohypothalamic innervation patterns predict the developmental emergence of species‐typical circadian phase preference in nocturnal Norway rats and diurnal nile grass rats

Abstract: How does the brain develop differently to support nocturnality in some mammals, but diurnality in others? To answer this, one might look to the suprachiasmatic nucleus (SCN), which is entrained by light via the retinohypothalamic tract (RHT). However, because the SCN is more active during the day in all mammals studied thus far, it alone cannot determine circadian phase preference. In adult Norway rats (Rattus norvegicus), which are nocturnal, the RHT also projects to the ventral subparaventricular zone (vSPVZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
(94 reference statements)
3
25
0
Order By: Relevance
“…This maturation of sleep characteristics as an organism develops from embryo to mature adult is referred to as sleep ontogeny or ontogenetic sleep changes. Similar trends, where the amount of total sleep, or vertebrate REM sleep, is highest early in development, have been observed in mammals, fish, birds, insects, and nematodes (Jouvet-Mounier et al 1970;McGinty et al 1977;Szymczak 1987;Shaw et al 2000;Kirov and Moyanova 2002;Paredes et al 2006;Raizen et al 2008;Hasan et al 2012;Todd et al 2012;Sorribes 2013). These findings led to the hypothesis that during early life, REM sleep and invertebrate sleep may play an important role in the development of the nervous system, by establishing a period of globally heightened plasticity and/ or providing endogenous, specialized activity in certain neural circuits (O'Donovan 1999;Blumberg 2008, 2010;Blumberg et al 2013;Corner 2013).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…This maturation of sleep characteristics as an organism develops from embryo to mature adult is referred to as sleep ontogeny or ontogenetic sleep changes. Similar trends, where the amount of total sleep, or vertebrate REM sleep, is highest early in development, have been observed in mammals, fish, birds, insects, and nematodes (Jouvet-Mounier et al 1970;McGinty et al 1977;Szymczak 1987;Shaw et al 2000;Kirov and Moyanova 2002;Paredes et al 2006;Raizen et al 2008;Hasan et al 2012;Todd et al 2012;Sorribes 2013). These findings led to the hypothesis that during early life, REM sleep and invertebrate sleep may play an important role in the development of the nervous system, by establishing a period of globally heightened plasticity and/ or providing endogenous, specialized activity in certain neural circuits (O'Donovan 1999;Blumberg 2008, 2010;Blumberg et al 2013;Corner 2013).…”
supporting
confidence: 62%
“…There are many arguments in support of the universality of sleep, but conservation of ontogenetic sleep changes with an active role in the developing nervous system is emerging as one of the strongest (Roffwarg et al 1966;Jouvet-Mounier et al 1970;McGinty et al 1977;Shaw et al 2000;Kirov and Moyanova 2002;Raizen et al 2008;Hasan et al 2012;Todd et al 2012;Sorribes 2013;Kayser et al 2014). The observation that sleep amount is highest during developmental periods across species has led to extensive and ongoing explorations of the ontogenetic hypothesis, suggesting that sleep promotes normal brain development by providing necessary endogenous activity (Roffwarg et al 1966;Jouvet-Mounier et al 1970;Oksenberg et al 1996;Shaffery et al 1999;Frank 2011;Blumberg et al 2013;Kayser et al 2014;Tononi and Cirelli 2014).…”
Section: A Link Between Development and The Ubiquity Of Sleep?mentioning
confidence: 99%
“…The vSPVZ [23,31,32], DMH [31], LC [33], and DR [27,34] exhibit a Fos response to light, with orexin being necessary for this response in the DR of grass rats [34]. As shown here, these areas responded to light in control grass rats, but not in animals with IGL lesions.…”
Section: Discussionmentioning
confidence: 84%
“…We discovered a general pattern such that nocturnal species, such as Norway rats, possess a strong direct connection between the RHT and the vSPVZ, and diurnal species, such as grass rats, lack a strong direct connection. This analysis also suggested that the maturity of young at birth (i.e., altriciality vs. precociality) and the timing of RHT development (i.e., prenatal vs. postnatal) modulate the functioning of this connection and the development of species-typical circadian preference (Todd et al, 2012). Additional work in a diversity of species is needed to rigorously test our hypothesis and assess the downstream consequences of species differences in RHT connectivity for other neural structures.…”
Section: Circadian Sleep-wake Rhythms: Development and Evolutionmentioning
confidence: 90%
“…Similar to Norway rats, the day-night sleep-wake pattern of grass rats emerged over the first two postnatal weeks: the initially slightly longer daytime wake bouts at P2 became substantially longer between P8 and P15 (Todd et al, 2012). Next, using Fos immunohistochemistry, we compared day-night differences in neural activity at P8 and P15 within the SCN and an interconnected adjacent structure, the ventral subparaventricular zone (vSPVZ).…”
Section: Circadian Sleep-wake Rhythms: Development and Evolutionmentioning
confidence: 94%